Comparing flow experience in using digital libraries: Web and mobile context. Issue 1 (16th March 2015) - Zha, Xianjin; Zhang, Jinchao; Yan, Yalan; Wang, Wentao
Abstract : Purpose: – Flow experience is conceptualized as an optimal experience about an activity, characterized by a match between perceived challenges and perceived skills. The purpose of this paper is to explore mobile libraries by comparing users' perceptions of web digital libraries and mobile libraries in terms of flow experience so as to obtain insights regarding the healthy development of mobile libraries. Design/methodology/approach: – Data collected from university digital library users were used for analysis. One figure was used to present the exact nature of users' perceptions of flow experience in terms of data distribution. The paired samples t -test was used to present the exact mean difference between flow experience in using web digital libraries and mobile libraries. Findings: – Fewer users can experience flow and more users cannot experience flow in using mobile libraries than in using web digital libraries. The mean of flow experience in using mobile libraries is significantly smaller than that in using web digital libraries. Practical implications: – Digital libraries have faced severe competition in the modern information society. In China university libraries as a whole are undergoing the transition from web digital libraries to mobile libraries. It is critical to examine user experience in the initial or early stage of mobile library development. The authors believe the findings of this study regarding flow experience provide useful insights for facilitating the healthy development of mobile libraries. Originality/value: – This study explores and compares users' perceptions of web digital libraries and mobile libraries in terms of flow experience, which the authors think provides a new view for university digital library research and practice alike.